2017
DOI: 10.1042/bcj20170256
|View full text |Cite
|
Sign up to set email alerts
|

The human RNA-binding protein RBFA promotes the maturation of the mitochondrial ribosome

Abstract: Accurate assembly and maturation of human mitochondrial ribosomes is essential for synthesis of the 13 polypeptides encoded by the mitochondrial genome. This process requires the correct integration of 80 proteins, 1 mt (mitochondrial)-tRNA and 2 mt-rRNA species, the latter being post-transcriptionally modified at many sites. Here, we report that human ribosome-binding factor A (RBFA) is a mitochondrial RNA-binding protein that exerts crucial roles in mitoribosome biogenesis. Unlike its bacterial orthologue, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 53 publications
(72 reference statements)
4
34
0
1
Order By: Relevance
“…As GTPBP10 is present in mitochondria and has been suggested to be required for mitochondrial OXPHOS function ( 20 ), we asked whether GTPBP10 is maintained in OXPHOS deficient cells lacking mtDNA (rho 0 ). Interestingly, GTPBP10 is significantly reduced in rho 0 cells (Figure 2A ), which is reminiscent to other proteins required for mitochondrial gene expression including MRPs and ribosome biogenesis factors such as MALSU1, DDX28 or mtRBFA ( 23 , 24 ).…”
Section: Resultsmentioning
confidence: 98%
“…As GTPBP10 is present in mitochondria and has been suggested to be required for mitochondrial OXPHOS function ( 20 ), we asked whether GTPBP10 is maintained in OXPHOS deficient cells lacking mtDNA (rho 0 ). Interestingly, GTPBP10 is significantly reduced in rho 0 cells (Figure 2A ), which is reminiscent to other proteins required for mitochondrial gene expression including MRPs and ribosome biogenesis factors such as MALSU1, DDX28 or mtRBFA ( 23 , 24 ).…”
Section: Resultsmentioning
confidence: 98%
“…Notably, these proteins were initially characterised as mitochondrial transcription factors [ 37 ]; however, in vivo analyses revealed that TFB1M is primarily responsible for modification of 12S rRNA, while TFB2M mainly functions as a transcription factor (reviewed in [ 38 ]). Interestingly, ribosome-binding factor A (RBFA) was recently found to bind directly to the region of the 12S rRNA that contains these dimethylations and to be required for their efficient installation [ 39 ]. Lack of in the SSU rRNA of bacteria and yeast does not significantly affect SSU biogenesis, but rather, these modifications have been implicated in maintaining translation efficiency by the ribosome or conferring increased sensitivity to antibiotics [ 40 ].…”
Section: Mt-rrna Modificationsmentioning
confidence: 99%
“…Additionally to the mitochondrial proteins (with above mentioned exceptions) the complex of METTL15 with the small ribosomal subunit assembly intermediate contained RBFA [ 13 ]. This protein was previously demonstrated to function as an assembly factor for the small mitoribosomal subunit [ 105 ], whose absence, albeit almost neutral for the efficiency of mitochondrial translation, lead to substoichiometric 12S rRNA methylation by TFB1M. In bacteria the function of RbfA homologue is better studied.…”
Section: Common Modified Nucleotides In Mitochondrial and Bacteriamentioning
confidence: 99%
“…It might be hypothesized that a complex of bacterial 30S subunit precursor bound to RbfA might be a substrate of RsmH, similar to that for the mitochondrial RBFA and METTL15 proteins. In addition to RBFA, methyltransferase TFB1M which is engaged to the late steps of the SSU assembly and whose activity is stimulated by RBFA [ 105 ] was also found coprecipitating with METTL15 [ 13 ]. Another mitochondrial rRNA methyltransferase, NSUN4, was found to act inefficiently upon inactivation of METTL15 gene [ 10 , 12 , 13 ], which is discussed in a previous section.…”
Section: Common Modified Nucleotides In Mitochondrial and Bacteriamentioning
confidence: 99%